2020
DOI: 10.1186/s12302-020-00312-x
|View full text |Cite
|
Sign up to set email alerts
|

Chemicals of emerging concern in marine specimens of the German Environmental Specimen Bank

Abstract: Background: Descriptor 8 of the Marine Strategy Framework Directive (MSFD) (Directive 2008/56/EC) addresses the good environmental status with regard to pollution of marine waters by chemical contaminants. Commission decision (EU) 2017/848 lays down the criteria and methodological standards on good environmental status of marine waters. Member States, in regional or subregional cooperation, shall establish lists of relevant contaminants beside those already covered by the Water Framework Directive (WFD). To pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Concentrations are in ng/L. (Fliedner et al, 2020;Loos et al, 2018). Within the present study, two of these pharmaceuticals, namely clarithromycin and diclofenac, were included in the screening and were quantified in 2% and 7% of the samples respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations are in ng/L. (Fliedner et al, 2020;Loos et al, 2018). Within the present study, two of these pharmaceuticals, namely clarithromycin and diclofenac, were included in the screening and were quantified in 2% and 7% of the samples respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The MSFD and the WFD were designed as a holistic policy to protect marine and freshwater environments around Europe and enable their sustainable use of goods and services. In the specific case of marine coastal zones, there is an overlap between both directives, since the main source of contaminants in marine environments are originated in land-based facilities and from freshwater systems [19].…”
Section: Emerging Contaminants In Marine Coastal Zonesmentioning
confidence: 99%
“…CECs include substances that are not regulated by EPA or EU Norman network including a diverse range of chemicals and their sub-products that are classified under a variety of group categories. The most common groups are flame retardants, antifoulants, anticorrosion agents, polyfluoroalkyl substances other than PFOS and PFOA, benzotriazoles or siloxanes [19]; also, pharmaceuticals, antibiotics, personal care products and illicit drugs [27][28][29][30], as well as, microplastics, trace metals, nanomaterials and pesticides [31,32]. While PhaCs have been the most prominent emerging pollutants for decades, PCPs have gained great attention in the last 5-10 years, given the wide and varied use of daily care products by the population.…”
Section: Emerging Contaminants In Marine Coastal Zonesmentioning
confidence: 99%
“…Recent research has proven that PFAS are present at high concentrations in organisms from both lower and upper trophic levels (Androulakakis et al, 2022;Butt et al, 2010;De Silva et al, 2021;Muir et al, 2019). The presence of PFAS in aquatic organisms of lower trophic levels is well-reported (Catherine et al, 2019;Fliedner et al, 2020), and recently the scientific interest has shifted to the investigation of their occurrence at higher trophic levels of the terrestrial and aquatic food webs (Fujii et al, 2018;Li et al, 2018;Sedlak et al, 2017;Spaan et al, 2020;Wu et al, 2020). For example, through the target analysis of PFAS in 140 liver samples of Eurasian Otters (Lutra lutra) gathered from Scandinavia from 1972 till 2011, Roos et al (2013) observed increasing trends in nine PFAS and extremely high concentrations of Perfluorooctanesulfonic acid (PFOS) which supports the concern of trophic magnification.…”
Section: Introductionmentioning
confidence: 99%